Computed Radiographic Studies on the Vertebral Heart Score in Pugs with Haematological and Serum Biochemical Correlations - Swetha, P. (Indian Journal of Veterinary Anatomy, 2020)
Computed radiographic (CR) studies were conducted to determine the Vertebral Heart Score (VHS) in 18 clinically healthy Pugs divided into three age groups viz. group-I (< 6 months), group-II (7-12 months) and group-III (>12 months) with six animals in each. They were subjected to thoracic radiography in left lateral, right lateral and dorsoventral views to estimate the cardiac size both with inbuilt Veterinary specific software and by manual measurements. The size of the heart increased from age of 6 months to >12 months and the variation in the size of the heart was not significant in the three age groups. Significantly higher Vertebral Heart Score values were observed on the right lateral projection than on left lateral projection in both CR and manual methods in all the age groups. The manual VHS values were higher compared to the CR values in both lateral views. There was no correlation between the body weight and the VHS values among all the three age groups. The dogs were evaluated for their haematological and serum biochemical parameters to ascertain their normal health status.